Pengukuran User Experience Pada Aplikasi Simulasi Kebakaran Keselamatan Dan Kesehatan Kerja Berbasis Augmented Reality - Bisma Khairunnas; Riwinoto Riwinoto (Politeknik Negeri Batam, 2022)
Occupational safety and health is very important to learn, one of which is fire disaster management. But to do learning in fire management, it takes time and adequate space. Fire simulation application is an application that utilizes augmented reality technology to facilitate users in learning and understanding how to deal with fire disasters if they occur indoors. However, to make fire simulation applications attractive and make users feel satisfied, user experience measurements must be made to determine the level of user satisfaction. To get user experience measurements, research was conducted using the Quality in use Integrated Measurement (QUIM) method where this method determines quality requirements such as identifying, analyzing, and validating processes and quality metrics in augmented reality-based fire simulation applications. QUIM which has 10 consolidated model factors for its assessment, namely efficiency, effectiveness, satisfaction, productivity, learnability, safety, trustfulness, accessibility, universality, and usefulness. data collection by means of users will test the application first. After that, a questionnaire will be given, this is done in a closed manner where users can only answer